Promising long-term outcomes ffter pelvic exenteration - Kulu, Yakup; Mehrabi, Arianeb; Khajeh, Elias; Klose, Johannes; Greenwood, Johanna; Hackert, Thilo; Büchler, Markus W.; Ulrich, Alexis (Annals of surgical oncology, 2019)
BackgroundPelvic exenteration (PE) is a complex and challenging surgical procedure. The reported results of this procedure for primary and recurrent disease are limited and conflicting.MethodsThis study analyzed patient outcomes after all PEs performed in the authors’ department between October 2001 and December 2016. Relevant patient data were obtained from a prospective database. Morbidity and mortality were reported for all patients. For patients with malignant disease, differences in perioperative outcomes, prognostic indicators for overall survival, and local and systemic disease recurrence were analyzed using uni- and multivariate analyses.ResultsThe study enrolled 187 patients. Of the 183 patients with malignant disease, 63 (38.2%) had primary locally advanced tumors and 115 (62.5%) had recurrent tumors. The 10-year overall survival rate was 63.5% for the patients with primary tumors that were curatively resected and 20.9% for the patients with recurrent disease (p = 0.02). The 10-year survival rate for the patients with extrapelvic disease who underwent curative resection was 37%. Multivariable analysis identified margin positivity (p < 0.01), surgery lasting longer than 7 h (p = 0.02), and recurrent disease (p < 0.01) as predictors of poor survival. Multivariate analysis of local and systemic disease recurrence showed recurrent disease (p < 0.01) as the only significant prognostic factor.ConclusionsPelvic exenteration has good long-term results, even for patients with extrapelvic disease. The oncologic outcome for patients with recurrent disease is worse than for patients with primary disease. However, even for these patients, long-time survival is possible.